2022
DOI: 10.3389/fvets.2022.912224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of African Swine Fever Virus From 2019-2020 Outbreaks in Guangxi Province, Southern China

Abstract: African swine fever virus (ASFV) causes contagious hemorrhagic disease of pigs with high morbidity and mortality. To identify the molecular characteristics of ASFV strains circulating in Guangxi province, southern China, a total of 336 tissue samples collected from 336 domestic pigs that died as a result of severe hemorrhagic disease during 2019–2020 were tested for ASFV. Furthermore, 66 ASFV strains were genetically characterized by sequence analysis of the C-terminal region of B646L (p72) gene, the complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
0
21
4
Order By: Relevance
“…A recent study revealed that a tandem repeat sequence (TRS) located in the intergenic region between I73R and I329L can be used to determine the origin of ASFV isolates ( 18 ). Additionally, the analysis of other sequences, such as EP402R and E183L , may help improve molecular epidemiological studies of ASFV ( 19 , 20 ). To better understand and control the spread of ASF, it is necessary to analyze the genetic characteristics of ASFV strains.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that a tandem repeat sequence (TRS) located in the intergenic region between I73R and I329L can be used to determine the origin of ASFV isolates ( 18 ). Additionally, the analysis of other sequences, such as EP402R and E183L , may help improve molecular epidemiological studies of ASFV ( 19 , 20 ). To better understand and control the spread of ASF, it is necessary to analyze the genetic characteristics of ASFV strains.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ASFVs from Romania were grouped into 6 distinct groups ( 3 , 7 , 19 , 21 , 23 , 24 ). Interestingly, the 2019 epidemic wave, despite taking place in a short space of time ( 40 ), was caused by two distinct genetic groups specific only to Romania.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the resolving power of this gene region in isolates from Africa ( 28 34 ) and the polymorphisms observed in isolates from Estonia ( 14 ), only two SNP-based CVR variants were detected in this study in wild boar viruses from Poland (CVR1-SNP2) and Lithuania (CVR1-SNP3). Recent studies describe the presence of additional CVR variants in isolates from Russia ( 35 ) and China ( 19 ) based on the presence of SNPs. However, the variants described in this study were unique and were not further identified in any of the ASFVs sequenced or available in the GenBank.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations